Fostering Science-themed Reading Comprehension of Elementary Students: The Effect of Digital Simulations and Content and Language Integrated Learning - Adin Fauzi; Fu’ad Sholiki; Dian Fadhilawati; Muhamad Kevin Akbar, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
While integrated learning is not a novel concept, it continues to capture attention. For instance, in elementary schools, merging English content with science is gaining traction. Successful implementation requires innovative media and relevant approaches. This study explores the effect of employing digital simulation media using a Content and Language Integrated Learning (CLIL) approach on sixth-grade students' comprehension of science-themed English texts. This research, employing a quasi-experiment with a one-group pretest-posttest design, involved 17 elementary school students. They underwent pretest, treatment, and posttest stages, with tests as the main data collection tool, validated and deemed suitable for use. Statistical analysis using the t-test in the SPSS software revealed a p-value of < 0.001, lower than 0.05, leading to the rejection of the null hypothesis. In essence, the use of digital simulation media with a CLIL approach significantly influences students' ability to understand science-themed English texts. Pedagogically, these findings suggest teaching alternatives with the potential to enhance both reading skills and science understanding. The integration of digital simulation media and the CLIL approach adds an engaging dimension to the learning process